Teachers’ acculturation in culturally diverse schools - How is the perceived diversity climate linked to intercultural self-efficacy? - Ulbricht, Jolina; Schachner, Maja K.; Civitillo, Sauro; Noack, Peter (Frontiers in Psychology, 2022)
While in the school context, acculturation is often studied in relation to students of immigrant descent, the current study applies an acculturation framework to teachers mostly representing the mainstream culture. Specifically, we investigate whether teachers’ acculturation attitudes towards their students mediate effects of the perceived cultural diversity climate at school on teachers’ self-efficacy in culturally diverse classrooms. Analyses are based on reports of 186 teachers (14% of immigrant descent; Mage = 40.8; SDage = 11.8, 73% female) in 22 culturally diverse secondary schools in Southwest Germany. Path analyses indicate that perceived norms of cultural pluralism, and perceived norms of equality and inclusion are directly and positively associated with facets of intercultural self-efficacy. Moreover, teachers’ acceptance for cultural maintenance amongst their students is associated with intercultural self-efficacy, but no mediation was found between climate and intercultural self-efficacy via acculturation attitudes. Implications for teacher training, educational practice and future research on the acculturation and adjustment of teachers in culturally diverse classrooms will be discussed.